Algunas notas sobre las limitaciones de la Economía Matemática - Rivas Santos, Pablo (2013)
This article shows that the mathematical method to study economics is a system of knowledge from false assumptions and leading to erroneous conclusions. The Price Statistics is a way of representing historical realities of Prices. The Statistics of Prices is economic history, so the price indices are economic history data. Mathematical economists to address the relationship of prices and costs ignore the operation of the market and intend to leave aside the use of money (ingredient of economic calculation). However, implicitly assume the existence of money and its use, as talk (in general) of prices and costs, claiming confront cost prices. Prices are monetary magnitudes, and costs expressed in monetary terms only enter into economic calculation. Other mathematical economists assert that economic calculation would be based on units of utility. In Economics warned that people consciously want to bring about change. We know the forces driving change and such knowledge (based on reasoning) allows us to understand the economic process. The economist warns that what drives and causes the emergence of the market. With that knowledge fails to distinguish economic phenomena of physical phenomena may, by such a route, discover the laws governing the activities of the market. In the field of monetary economics Microeconomics and negative effects are noticed mathematical analysis: The “quantity equation of money” is a barren and misguided attempt to address the problem of variations in the purchasing power of money. The statement “consumers, to assess consumer goods also value the factors of production necessary for the production of these consumer goods “is a false assumption to microecomico analysis. The Economy is interested, directly by the people act. The only task of economic science is to analyze the actions of the people, that is, to analyze processes.